The industrialised building systems (IBS) in construction building project / Asmah Alia Mohamad Bohari, Kumalasari Kipli and Noorsaidi Mahat - Mohamad Bohari, Asmah Alia; Kipli, Kumalasari; Mahat, Noorsaidi (2012)
The Industrialized Building System (IBS) has known to give more benefits and far reaching to the construction industry in term of meeting the project objectives, which are to reduced construction time, high quality, standardized, reduce construction wastage and usage of labour and better site management which a few of these benefit will definitely produce better products for the client and its end user. The Malaysian government has spared no effort to bring IBS to the drawing tables of all professionals involved in the built environment. The IBS Roadmap 2003 -2010 has been endorsed by the Cabinet to be the blueprint document for the industrialization of the Malaysian construction sector. However, towards the last two years of the roadmap period, the effort to promote the usage of IBS as an alternative to conventional and labour intensive construction method is still far ahead. One of the efforts is through levy fees exemption/ Levy imposes to the contractors for project worth RM500, 000.00 and above with a condition the IBS content score is being implemented at least 50 % (IBS Roadmap Review, 2007).